Investigating the Prognostic and Oncogenic Roles of Membrane-Associated Ring-CH-Type Finger 9 in Colorectal Cancer - Jiayan Zhang; Qinghan Jiao; Zhigang Chen (Genetics Research)
Backgroundsand Aims. Colorectal cancer (CRC) represents a major global health challenge, necessitating comprehensive investigations into its underlying molecular mechanisms to enhance diagnostic and therapeutic strategies. This study focuses on elucidating the oncogenic role of Membrane-Associated Ring-CH-Type Finger 9 (MARCHF9), a RING-Type E3 ubiquitin transferase, in CRC. We aim to assess MARCHF9’s clinical significance, functional impact on CRC progression, and its potential as a prognostic biomarker. Methods. We leveraged data from the Cancer Genome Atlas (TCGA) cohort to evaluate MARCHF9 expression profiles in CRC. In vitro experiments involved siRNA-mediated MARCHF9 knockdown in COAD cell lines (SW480 and LoVo). Cell proliferation and invasion assays were conducted to investigate MARCHF9’s functional relevance. Survival analyses were performed to assess its prognostic role. Results. Our analysis revealed significantly elevated MARCHF9 expression in CRC tissues compared to normal colorectal tissues (P<0.05). High MARCHF9 expression correlated with advanced clinical stages, distant metastases, and the presence of residual tumors in CRC patients. Survival analyses demonstrated that high MARCHF9 expression predicted unfavorable overall and disease-free survival outcomes (P<0.05). In vitro experiments further supported its oncogenic potential, with MARCHF9 knockdown inhibiting COAD cell proliferation and invasion. Conclusions. This study unveils the oncogenic role of MARCHF9 in CRC, highlighting its clinical relevance as a potential biomarker and therapeutic target. MARCHF9’s association with adverse clinicopathological features and its functional impact on cancer cell behavior underscore its significance in CRC progression. Further research is essential to elucidate precise mechanisms by which MARCHF9 enhances tumorigenesis and to explore its therapeutic potential in CRC management.